2019
DOI: 10.1039/c8ta09637f
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of CO2 to formate on amine modified Pb electrodes

Abstract: Grafting of polyarylene layers on the surface of Pb electrodes improves their selectivity for the CO2 reduction to formate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…Particularly, formate with a high hydrogen content is usually used as liquid fuel in fuel cells. Moreover, formate can also be directly used for fabric processing, tanning, textile printing, and silage storage, as well as metal surface treatment agents, rubber additives, and industrial solvents [5,[15][16][17][18]. Nonetheless, the CO2RR process is generally accompanied by high energy consumption owing to the sluggish kinetics and low selectivity toward formate production.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, formate with a high hydrogen content is usually used as liquid fuel in fuel cells. Moreover, formate can also be directly used for fabric processing, tanning, textile printing, and silage storage, as well as metal surface treatment agents, rubber additives, and industrial solvents [5,[15][16][17][18]. Nonetheless, the CO2RR process is generally accompanied by high energy consumption owing to the sluggish kinetics and low selectivity toward formate production.…”
Section: Introductionmentioning
confidence: 99%
“…However, surface engineering at a heterogeneous catalyst for enhancing CO2R selectivity is relatively easy. The sluggish oxygen evolution kinetics occurring at an anode (as it involves a four-electron transfer) limits the overall CO2R efficiency [28].…”
Section: Homogeneous Catalysts For Co2rmentioning
confidence: 99%
“…The identity of the electrode used has been found to have a large inuence on the catalytic activity of homogeneous amine solutions, with different electrodes such as glassy carbon, copper, and silver each eliciting their own distinctive response. 18,46,55,63,[96][97][98][99][100][101] Lue et al 55 reported a systematic study on electrochemical CO 2 reduction with 30% (w/w) MEA on, Sn, Pb, Pd, Ag, Cu and Zn metal electrodes. Schmitt et al 100 used in situ surface-enhanced Raman spectroscopy to study 3,5-diamino-1,2,4-triazole (DAT) exposed-Ag electrodes, nding that the amine treated electrode increased FE CO due to a weakening of the CO bonding strength.…”
Section: Homogeneous Amine Molecular Catalysts and Electrochemical Comentioning
confidence: 99%
“…Zouaoui et al 97 investigated the electrocatalytic activity of amine derivatives deposited onto Pb surfaces toward electroreduction of CO 2 to formate. Using diazonium chemistry, 4aminomethylbenzene (4-ABA), 3-aminomethylbenzene (3-ABA), 4-(2-aminoethyl)benzene (4-AEA) and 4-nitrobenzene (4-NB) were graed onto Pb electrodes (Fig.…”
Section: Heterogeneous Amine Molecular Catalysts and Electrochemical mentioning
confidence: 99%